Penguatan ekonomi kreatif melalui edukasi dan pendampingan sertifikasi halal di perumahan pondok mutiara asri desa Pandanlandung - hidayah, hikmatul (Maliki Interdisciplinary Journal, 2026)
Community-based creative economy in Pondok Mutiara Asri Housing, Pandanlandung Village, has flourished since the COVID-19 pandemic by utilizing WhatsApp groups as transaction media. However, the majority of food and beverage MSMEs in the area lack halal certification, despite the diverse religious background of the residents. This study aims to describe the process of education and halal certification assistance as an effort to strengthen the creative economy. The method used is descriptive qualitative through observation, interviews, and direct assistance within the Halal Center Student Community Service (KKM) program of UIN Malang. The results show that intensive assistance successfully transformed the mindset of business actors who were initially skeptical of bureaucratic complexity into being aware of the importance of halal product assurance. The concrete impact of this program is the issuance of 14 halal certificates through the self-declare system on the SIHALAL application. Besides enhancing cognitive and administrative aspects, this certification provides added value in the form of professionalism and higher consumer trust. This success proves that digital independence in managing business legality is key to MSME competitiveness in the modern market. It is concluded that synergy between academics and business actors is highly effective in strengthening the local economic structure. Therefore, sustainable assistance is needed so all creative economy potential in the region can be fully certified.